Polymer solid electrolyte-negative electrode integrated structure, preparation method thereof and solid-state battery
Through the formation of MOF materials in the polymer solid electrolytes and performing microwave activation, the problem of limited lithium ion transmission channels and poor interface contacts were solved, and the cycle stability of solid electrolyte was significantly improved and the lithium ion diffusion coefficient was significantly improved.
Patent Information
- Application Number
- CN202411898066.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The lithium ion transmission channels inside the solid electrolyte of polymer are limited, and the crystal regions formed by long-chain organic polymers limit the transmission of lithium ions, and the interface contactability is poor, resulting in current density aggregation, intensified side reactions, and poor cycle stability.
By mixing the polymer, metal salt and lithium salt, the film formation treatment is performed to form a solid electrolyte layer of the polymer, and the aggregation reaction of the accelerated MOF material in the microwave activation processing is formed The uniform distribution of MOF materials.
By increasing lithium ion transmission channels and improving interface contact status, the lithium ion diffusion coefficient and cycle stability of solid electrolyte are significantly improved.
Smart Images

Figure CN119381581A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries, and specifically relates to an integrated structure of a polymer solid electrolyte-negative electrode and a preparation method thereof, and a solid-state battery. Background Art
[0002] The core difference between solid-state batteries and traditional liquid batteries lies in the difference in electrolytes. In solid-state batteries, solid electrolytes replace liquid electrolytes and separators, which not only reduces the weight and volume of the battery pack, but also significantly improves safety. Compared with traditional liquid electrolytes, solid electrolytes have the advantages of higher energy density, faster charging speed, and higher safety. At present, solid electrolytes mainly focus on three major technical routes: polymer, oxide and sulfide electrolytes. Among them, polymer solid electrolytes have good flexibility and processability, and can be wound and stacked like traditional lithium batteries, which has unique advantages. However, polymer solid electrolytes also face a series of problems. The lithium ion transmission channels and paths inside the polymer solid electrolyte are limited, and the crystalline regions formed by long-chain organic polymers will further limit the transmission of lithium ions. In addition, the interface contact of polymer solid electrolytes is poor, and the uncertainty of the interface state leads to current density aggregation, aggravated side reactions, and poor cycle stability. Summary of the invention
[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide an integrated structure of a polymer solid electrolyte-negative electrode and a preparation method thereof, as well as a solid-state battery.
[0004] To achieve the above objectives, the present invention provides the following specific technical solutions.
[0005] In a first aspect, the present invention provides a method for preparing an integrated structure of a polymer solid electrolyte-negative electrode.
[0006] First, the present invention provides a method for preparing an integrated structure of a polymer solid electrolyte-negative electrode, comprising: Adding a polymer, a metal salt, and a lithium salt into a solvent and mixing them to obtain a mixture I; subjecting the mixture I to a film-forming treatment to obtain a positive electrode side solid electrolyte layer; Adding a polymer, a ligand, and a lithium salt into a solvent and mixing them to obtain a mixture II; coating the mixture II on one surface of a solid electrolyte layer on the positive electrode side to obtain a polymer solid electrolyte layer; The metal salt is at least one of nitrates and sulfates of Co, Mn, Ni, and Zn; The ligand is at least one of 2-methylimidazole, imidazole, and ethylenediaminetetraacetic acid; The non-positive electrode side solid electrolyte layer of the polymer solid electrolyte layer is laminated to the lithium foil, and then subjected to microwave activation treatment to obtain an integrated structure of the polymer solid electrolyte-negative electrode.
[0007] Secondly, the present invention further provides a method for preparing an integrated structure of a polymer solid electrolyte-negative electrode, comprising: Adding the polymer, the metal salt and the lithium salt into the solvent and mixing them to obtain a mixture I; Adding the polymer, the ligand and the lithium salt into the solvent and mixing them to obtain a mixture II; The mixed material II is coated on one surface of the lithium foil, and after drying, the mixed material I is coated on the dried surface of the mixed material II to obtain a polymer solid electrolyte layer-lithium foil structure; The metal salt is at least one of nitrates and sulfates of Co, Mn, Ni, and Zn; The ligand is at least one of 2-methylimidazole, imidazole, and ethylenediaminetetraacetic acid; The polymer solid electrolyte layer-lithium foil structure is subjected to microwave activation treatment to obtain an integrated structure of the polymer solid electrolyte-negative electrode.
[0008] Again, the present invention further provides a method for preparing an integrated structure of a polymer solid electrolyte-negative electrode, comprising: Adding a polymer, a metal salt, and a lithium salt into a solvent and mixing them to obtain a mixture I; subjecting the mixture I to a film-forming treatment to obtain a positive electrode side solid electrolyte layer; Adding a polymer, a ligand, and a lithium salt into a solvent and mixing them to obtain a mixture II; subjecting the mixture II to a film-forming treatment to obtain a negative electrode side solid electrolyte layer; The metal salt is at least one of nitrates and sulfates of Co, Mn, Ni, and Zn; The ligand is at least one of 2-methylimidazole, imidazole, and ethylenediaminetetraacetic acid; The positive electrode side solid electrolyte layer, the negative electrode side solid electrolyte layer and the lithium foil are sequentially laminated, and then subjected to microwave activation treatment to obtain an integrated structure of a polymer solid electrolyte-negative electrode.
[0009] In a further preferred embodiment, the polymer is at least one of PVDF, PVDF-HFP, and PVDF-CTFE.
[0010] In a further preferred embodiment, the lithium salt is at least one of LiFSI and LiTFSI.
[0011] In a further preferred embodiment, the solvent is at least one of N,N-dimethylformamide, N-methylpyrrolidone and tetrahydrofuran.
[0012] In a further preferred embodiment, in the mixture I, the concentration of the polymer is 90-140 g / L, the concentration of the lithium salt is 70-120 g / L, and the concentration of the metal salt is 20-50 mmol / L.
[0013] In a further preferred embodiment, in the mixture II, the concentration of the polymer is 90-140 g / L, the concentration of the lithium salt is 70-120 g / L, and the concentration of the ligand is 21-57.5 mmol / L.
[0014] In a further preferred embodiment, the thickness of the positive electrode side solid electrolyte layer is 10-20 μm; the thickness of the negative electrode side solid electrolyte layer is 10-20 μm; and the thickness of the polymer solid electrolyte layer is 20-40 μm.
[0015] In a further preferred embodiment, the microwave activation is performed in a vacuum or inert atmosphere; the microwave intensity of the microwave activation is 4-10 mW; the microwave activation time is 1-2 h. Further preferably, the inert atmosphere is argon.
[0016] In a second aspect, the present invention provides an integrated structure of a polymer solid electrolyte-negative electrode prepared by the aforementioned preparation method.
[0017] In a third aspect, the present invention provides a solid-state battery comprising the aforementioned integrated structure of polymer solid electrolyte-negative electrode.
[0018] The beneficial effects that can be achieved by the above one or more technical solutions of the present invention will be reflected through specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the cycle performance curve of the battery. DETAILED DESCRIPTION
[0020] In a first aspect, the present invention provides a method for preparing an integrated structure of a polymer solid electrolyte-negative electrode.
[0021] First, some embodiments of the present invention provide a method for preparing an integrated structure of a polymer solid electrolyte-negative electrode, comprising: Adding a polymer, a metal salt, and a lithium salt into a solvent and mixing them to obtain a mixture I; subjecting the mixture I to a film-forming treatment to obtain a positive electrode side solid electrolyte layer; Adding a polymer, a ligand, and a lithium salt into a solvent and mixing them to obtain a mixture II; coating the mixture II on one surface of a solid electrolyte layer on the positive electrode side to obtain a polymer solid electrolyte layer; The metal salt is at least one of nitrates and sulfates of Co, Mn, Ni, and Zn; The ligand is at least one of 2-methylimidazole, imidazole, and ethylenediaminetetraacetic acid; The non-positive electrode side solid electrolyte layer of the polymer solid electrolyte layer is laminated to the lithium foil, and then subjected to microwave activation treatment to obtain an integrated structure of the polymer solid electrolyte-negative electrode.
[0022] Secondly, some embodiments of the present invention provide a method for preparing an integrated structure of a polymer solid electrolyte-negative electrode, comprising: Adding the polymer, the metal salt and the lithium salt into the solvent and mixing them to obtain a mixture I; Adding the polymer, the ligand and the lithium salt into the solvent and mixing them to obtain a mixture II; The mixed material II is coated on one surface of the lithium foil, and after drying, the mixed material I is coated on the dried surface of the mixed material II to obtain a polymer solid electrolyte layer-lithium foil structure; The metal salt is at least one of nitrates and sulfates of Co, Mn, Ni, and Zn; The ligand is at least one of 2-methylimidazole, imidazole, and ethylenediaminetetraacetic acid; The polymer solid electrolyte layer-lithium foil structure is subjected to microwave activation treatment to obtain an integrated structure of the polymer solid electrolyte-negative electrode.
[0023] Again, some embodiments of the present invention provide a method for preparing an integrated structure of a polymer solid electrolyte-negative electrode, comprising: Adding a polymer, a metal salt, and a lithium salt into a solvent and mixing them to obtain a mixture I; subjecting the mixture I to a film-forming treatment to obtain a positive electrode side solid electrolyte layer; Adding a polymer, a ligand, and a lithium salt into a solvent and mixing them to obtain a mixture II; subjecting the mixture II to a film-forming treatment to obtain a negative electrode side solid electrolyte layer; The metal salt is at least one of nitrates and sulfates of Co, Mn, Ni, and Zn; The ligand is at least one of 2-methylimidazole, imidazole, and ethylenediaminetetraacetic acid; The positive electrode side solid electrolyte layer, the negative electrode side solid electrolyte layer and the lithium foil are sequentially laminated, and then subjected to microwave activation treatment to obtain an integrated structure of a polymer solid electrolyte-negative electrode.
[0024] In general, the preparation method provided by the present invention is to accelerate the MOF-like polymerization reaction inside the solid electrolyte under a microwave environment, form an in-situ MOF-like material in the solid electrolyte, and achieve uniform distribution of the MOF-like material. Due to the long-range ordered lithium ion transmission channel and nano-scale uniform distribution in the MOF-like material, it is beneficial to reduce the crystallization area and lithium ion channel construction in the solid electrolyte. In addition, a small amount of excess ligand material on the negative electrode side can form a certain artificial SEI film after contacting with lithium metal, which helps to improve the contact state of the interface and greatly improve the lithium ion diffusion coefficient and cycle stability of the battery.
[0025] (1) A polymer, a metal salt and a lithium salt are added to a solvent and mixed to obtain a mixture I; the metal salt is at least one of a nitrate and a sulfate of Co, Mn, Ni and Zn.
[0026] Adding metal salts to the electrolyte slurry on the positive electrode side can, on the one hand, react with the ligands in the electrolyte on the negative electrode side to produce ligand compounds similar to MOF materials at the interface of the positive and negative solid electrolytes after activation, thereby increasing the inward ionic conductivity of the body; and the MOF-like materials generated in situ in the electrolyte are smaller in size and better dispersed.
[0027] Moreover, MOF-like materials can further improve the mechanical properties of solid-state electrolytes and increase their ability to resist negative electrode lithium dendrites.
[0028] The present invention selects at least one of the nitrates and sulfates of Co, Mn, Ni, and Zn as the metal salt. These metals are transition metals and have elements similar to those in the positive electrode materials of lithium-ion batteries. They can inhibit the disproportionation reaction and dissolution of the positive electrode transition metal materials and increase the stability of the positive electrode interface.
[0029] (2) Adding a polymer, a ligand, and a lithium salt into a solvent and mixing them to obtain a mixture II; the ligand is at least one of 2-methylimidazole, imidazole, and ethylenediaminetetraacetic acid.
[0030] Adding ligands to the electrolyte slurry on the negative electrode side can, on the one hand, undergo a complex reaction with the metal ions in the solid electrolyte on the positive electrode side during the activation process; on the other hand, it can undergo a small amount of complex reaction with lithium metal at the solid-lithium metal interface during the activation process, thereby increasing the compatibility between the solid electrolyte and the positive electrode material.
[0031] (3) Perform microwave activation treatment.
[0032] On the one hand, microwave activation can increase the local temperature of the material, and on the other hand, it can increase the activity of ions or molecules, which is beneficial to improving the speed of polymer chain movement. At the same time, it accelerates the transfer and reaction between metal ions, ligands, and a small amount of residual solvent, promotes the reaction between metal ions and ligands in the solid electrolyte on the positive and negative electrode sides, and also promotes the interface reaction between lithium metal and the solid electrolyte.
[0033] In some specific embodiments of the present invention, the polymer is at least one of PVDF, PVDF-HFP, and PVDF-CTFE.
[0034] In some specific embodiments of the present invention, the lithium salt is at least one of LiFSI and LiTFSI.
[0035] In some specific embodiments of the present invention, the solvent is at least one of N,N-dimethylformamide, N-methylpyrrolidone and tetrahydrofuran.
[0036] In some specific embodiments of the present invention, in the mixture I, the concentration of the polymer is 90~140g / L, such as 90g / L, 100g / L, 110g / L, 120g / L, 130g / L, 140g / L; the concentration of the lithium salt is 70~120g / L, such as 70g / L, 80g / L, 90g / L, 100g / L, 110g / L, 120g / L; the concentration of the metal salt is 20~50mmol / L, such as 20mmol / L, 30mmol / L, 40mmol / L, 50mmol / L.
[0037] In some specific embodiments of the present invention, in the mixture II, the concentration of the polymer is 90~140g / L, such as 90g / L, 100g / L, 110g / L, 120g / L, 130g / L, 140g / L; the concentration of the lithium salt is 70~120g / L, such as 70g / L, 80g / L, 90g / L, 100g / L, 110g / L, 120g / L; the concentration of the ligand is 21~57.5mmol / L, such as 21mmol / L, 31.5mmol / L, 42mmol / L, 52.5mmol / L, 57.5mmol / L.
[0038] In some specific embodiments of the present invention, the thickness of the positive electrode side solid electrolyte layer is 10-20 μm; the thickness of the negative electrode side solid electrolyte layer is 10-20 μm; and the thickness of the polymer solid electrolyte layer is 20-40 μm.
[0039] In some specific embodiments of the present invention, the microwave activation is carried out in a vacuum or inert atmosphere; the microwave intensity of the microwave activation is 4-10 mW; and the time of the microwave activation is 1-2 h.
[0040] In a second aspect, some embodiments of the present invention provide an integrated structure of a polymer solid electrolyte-negative electrode prepared by the aforementioned preparation method.
[0041] In a third aspect, some embodiments of the present invention provide a solid-state battery comprising the aforementioned integrated structure of polymer solid electrolyte-negative electrode.
[0042] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0043] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0044] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0045] Example 1 (1) 10 g of PVDF-HFP, 9 g of LiFSI and 3 mmol of cobalt nitrate were added to 100 ml of N,N-dimethylformamide and stirred thoroughly to obtain a mixed slurry I; the mixed slurry I was evenly coated on a glass plate and dried thoroughly to obtain a positive electrode side solid electrolyte membrane with a thickness of 10 μm.
[0046] (2) Take 10 g of PVDF-HFP, 9 g of LiFSI and 3.3 mmol of 2-methylimidazole and add them to 100 ml of N,N-dimethylformamide, and stir and mix them thoroughly to obtain mixed slurry II; the mixed slurry II is evenly coated on one surface of the positive electrode side solid electrolyte membrane prepared in step (1) to obtain a polymer solid electrolyte layer with a thickness of 25 μm.
[0047] (3) The lithium foil is laminated to one side of the non-positive electrode side of the polymer solid electrolyte layer, and then activated in an argon atmosphere and an 8 mW microwave environment for 1.5 hours. After sufficient drying, an integrated structure of the polymer solid electrolyte-negative electrode is obtained.
[0048] Comparative Example 1 (1) 10 g of PVDF-HFP, 9 g of LiFSI and 3 mmol of cobalt nitrate were added to 100 ml of N,N-dimethylformamide and stirred thoroughly to obtain a mixed slurry I; the mixed slurry I was evenly coated on a glass plate and dried thoroughly to obtain a solid electrolyte membrane with a thickness of 25 μm.
[0049] (2) The lithium foil is laminated to the solid electrolyte membrane, and then activated in an argon atmosphere and an 8 mW microwave environment for 1.5 hours. After sufficient drying, an integrated structure of a polymer solid electrolyte-negative electrode is obtained.
[0050] Comparative Example 2 (1) 10 g of PVDF-HFP, 9 g of LiFSI and 3 mmol of cobalt nitrate were added to 100 ml of N,N-dimethylformamide and stirred thoroughly to obtain a mixed slurry I; the mixed slurry I was evenly coated on a glass plate and dried thoroughly to obtain a positive electrode side solid electrolyte membrane with a thickness of 10 μm.
[0051] (2) Take 10 g of PVDF-HFP, 9 g of LiFSI and 3.3 mmol of 2-methylimidazole and add them to 100 ml of N,N-dimethylformamide, and stir and mix them thoroughly to obtain mixed slurry II; the mixed slurry II is evenly coated on one surface of the positive electrode side solid electrolyte membrane prepared in step (1) to obtain a polymer solid electrolyte layer with a thickness of 25 μm.
[0052] (3) Laminating the lithium foil to one side of the non-positive electrode side solid electrolyte membrane of the polymer solid electrolyte layer to obtain an integrated structure of the polymer solid electrolyte-negative electrode.
[0053] Comparative Example 3 (1) 10 g of PVDF-HFP, 9 g of LiFSI and 3.3 mmol of 2-methylimidazole were added to 100 ml of N,N-dimethylformamide and stirred thoroughly to obtain a mixed slurry II; the mixed slurry II was evenly coated on a glass plate and dried thoroughly to obtain a solid electrolyte membrane with a thickness of 25 μm.
[0054] (2) The lithium foil was laminated to one side of the solid electrolyte membrane, and then activated in an argon atmosphere and an 8 mW microwave environment for 1.5 hours. After sufficient drying, an integrated structure of a polymer solid electrolyte-negative electrode was obtained.
[0055] Example 2 (1) 9 g of PVDF, 7 g of LiTFSI and 2 mmol of manganese nitrate were added to 100 ml of N-methylpyrrolidone and stirred thoroughly to obtain a mixed slurry I; (2) 9 g of PVDF, 7 g of LiTFSI and 2.3 mmol of imidazole were added to 100 ml of N-methylpyrrolidone and stirred thoroughly to obtain a mixed slurry II; (3) The mixed slurry II is uniformly coated on the surface of the lithium foil, and after drying, a negative electrode side solid electrolyte layer with a thickness of 10 μm is formed, thereby obtaining a negative electrode side solid electrolyte layer-negative electrode structure; (4) uniformly coating the mixed slurry I on the negative electrode side solid electrolyte layer of the negative electrode side solid electrolyte layer-negative electrode structure, and after drying, forming a solid electrolyte layer-negative electrode structure with a thickness of 30 μm together with the negative electrode side solid electrolyte layer; (5) The solid electrolyte layer-negative electrode structure obtained in step (4) was activated and reacted in a vacuum, 6 mW microwave environment for 2 hours, and after being fully dried, an integrated structure of a polymer solid electrolyte-negative electrode was obtained.
[0056] Example 3 (1) 12 g of PVDF-CTFE, 12 g of LiTFSI and 5 mmol of nickel nitrate were added to 100 ml of N-methylpyrrolidone and stirred thoroughly to obtain a mixed slurry I; (2) 12 g PVDF-CTFE, 12 g LiTFSI and 5.75 mmol ethylenediaminetetraacetic acid were added to 100 ml N-methylpyrrolidone and stirred thoroughly to obtain mixed slurry II; (3) The mixed slurry I is evenly coated on a glass plate and dried sufficiently to obtain a positive electrode side solid electrolyte membrane with a thickness of 20 μm.
[0057] (4) The mixed slurry II is evenly coated on a glass plate and dried sufficiently to obtain a negative electrode side solid electrolyte membrane with a thickness of 20 μm.
[0058] (5) The positive electrode side solid electrolyte membrane, the negative electrode side solid electrolyte membrane, and the lithium foil are laminated in sequence, and then activated and reacted in a vacuum, 10 mW microwave environment for 1 hour. After sufficient drying, an integrated structure of a polymer solid electrolyte-negative electrode is obtained.
[0059] Example 4 (1) 10 g of PVDF-CTFE, 10 g of LiTFSI and 3 mmol of zinc sulfate were added to 100 ml of N-methylpyrrolidone and stirred thoroughly to obtain a mixed slurry I; (2) 10 g PVDF, 12 g LiFSI and 3.15 mmol imidazole were added to 100 ml tetrahydrofuran and stirred thoroughly to obtain mixed slurry II; (3) The mixed slurry I was evenly coated on a glass plate and dried sufficiently to obtain a positive electrode side solid electrolyte membrane with a thickness of 15 μm.
[0060] (4) The mixed slurry II was evenly coated on a glass plate and dried sufficiently to obtain a negative electrode side solid electrolyte membrane with a thickness of 15 μm.
[0061] (5) The positive electrode side solid electrolyte membrane, the negative electrode side solid electrolyte membrane, and the lithium foil are laminated in sequence, and then activated and reacted in an argon atmosphere and a 10 mW microwave environment for 1 hour. After being fully dried, an integrated structure of a polymer solid electrolyte-negative electrode is obtained.
[0062] Test example: The integrated structures obtained in Examples 1-4 and Comparative Examples 1-3 were cut into discs with a diameter of 16 mm to serve as lithium negative electrodes and electrolytes.
[0063] The commercial six-series (622) ternary cathode material was mixed with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as the solvent. The mixture was stirred in a small beaker at a speed of 800r / min for 2h to obtain a slurry. The slurry was coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for 4h, punched into a circular electrode with a diameter of 12mm, and dried in a vacuum drying oven at 105°C for 4h to obtain a cathode.
[0064] In a glove box filled with argon atmosphere and having a water content and an oxygen content both lower than 0.01 ppm, the integrated structures obtained in Examples 1-4 and Comparative Examples 1-3 were cut into discs with a diameter of 16 mm, and the positive electrodes were assembled into CR2032 button batteries.
[0065] After the battery is assembled and aged for 12 hours, it is subjected to charge and discharge tests at different potentials: 100 cycles at a voltage of 2.8-4.3V and a current density of 0.5C.
[0066] The results are as follows Figure 1 As shown. As can be seen from the figure, after 100 cycles, the capacities of the batteries assembled with the integrated structure obtained in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 are 159.4 mAh / g, 2.2 mAh / g, 11.13 mAh / g, and 33.52 mAh / g, respectively. This shows that the ligand in the solid electrolyte slurry on the negative electrode side, the metal salt in the solid electrolyte slurry on the positive electrode side, microwave activation, etc. are crucial to improving the cycle performance of the battery and maintaining the capacity, and none of them can be missing. In addition, the batteries assembled with the integrated structure obtained in Example 2, Example 3, and Example 4 have capacities of 158.2 mAh / g, 163.2 mAh / g, and 164.6 mAh / g, respectively, after 100 cycles, with very good cycle performance and capacity retention.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an integrated structure of a polymer solid electrolyte-negative electrode, characterized in that: include: Adding a polymer, a metal salt, and a lithium salt into a solvent and mixing them to obtain a mixture I; subjecting the mixture I to a film-forming treatment to obtain a positive electrode side solid electrolyte layer; Adding a polymer, a ligand, and a lithium salt into a solvent and mixing them to obtain a mixture II; coating the mixture II on one surface of a solid electrolyte layer on the positive electrode side to obtain a polymer solid electrolyte layer; The metal salt is at least one of nitrates and sulfates of Co, Mn, Ni, and Zn; The ligand is at least one of 2-methylimidazole, imidazole, and ethylenediaminetetraacetic acid; The non-positive electrode side solid electrolyte layer of the polymer solid electrolyte layer is laminated to the lithium foil, and then subjected to microwave activation treatment to obtain an integrated structure of the polymer solid electrolyte-negative electrode.
2. A method for preparing an integrated structure of a polymer solid electrolyte-negative electrode, characterized in that: include: Adding the polymer, the metal salt and the lithium salt into the solvent and mixing them to obtain a mixture I; Adding the polymer, the ligand and the lithium salt into the solvent and mixing them to obtain a mixture II; The mixed material II is coated on one surface of the lithium foil, and after drying, the mixed material I is coated on the dried surface of the mixed material II to obtain a polymer solid electrolyte layer-lithium foil structure; The metal salt is at least one of nitrates and sulfates of Co, Mn, Ni, and Zn; The ligand is at least one of 2-methylimidazole, imidazole, and ethylenediaminetetraacetic acid; The polymer solid electrolyte layer-lithium foil structure is subjected to microwave activation treatment to obtain an integrated structure of the polymer solid electrolyte-negative electrode.
3. A method for preparing an integrated structure of a polymer solid electrolyte-negative electrode, characterized in that: include: Adding a polymer, a metal salt, and a lithium salt into a solvent and mixing them to obtain a mixture I; subjecting the mixture I to a film-forming treatment to obtain a positive electrode side solid electrolyte layer; Adding a polymer, a ligand, and a lithium salt into a solvent and mixing them to obtain a mixture II; subjecting the mixture II to a film-forming treatment to obtain a negative electrode side solid electrolyte layer; The metal salt is at least one of nitrates and sulfates of Co, Mn, Ni, and Zn; The ligand is at least one of 2-methylimidazole, imidazole, and ethylenediaminetetraacetic acid; The positive electrode side solid electrolyte layer, the negative electrode side solid electrolyte layer and the lithium foil are sequentially laminated, and then subjected to microwave activation treatment to obtain an integrated structure of a polymer solid electrolyte-negative electrode.
4. The preparation method according to any one of claims 1 to 3, characterized in that The polymer is at least one of PVDF, PVDF-HFP, and PVDF-CTFE; the lithium salt is at least one of LiFSI and LiTFSI; and the solvent is at least one of N,N-dimethylformamide, N-methylpyrrolidone, and tetrahydrofuran.
5. The preparation method according to claim 4, characterized in that: In the mixture I, the concentration of the polymer is 90-140 g / L, the concentration of the lithium salt is 70-120 g / L, and the concentration of the metal salt is 20-50 mmol / L; in the mixture II, the concentration of the polymer is 90-140 g / L, the concentration of the lithium salt is 70-120 g / L, and the concentration of the ligand is 21-57.5 mmol / L.
6. The preparation method according to any one of claims 1 to 3, characterized in that: The microwave activation is carried out in a vacuum or inert atmosphere; the microwave intensity of the microwave activation is 4-10 mW; and the time of the microwave activation is 1-2 h.
7. A polymer solid electrolyte-negative electrode integrated structure, characterized in that: The method is prepared by any one of claims 1 to 6.
8. A solid-state battery, characterized in that: An integrated structure comprising the polymer solid electrolyte-negative electrode as described in claim 7.
Citation Information
Patent Citations
Polymer composite solid electrolyte, preparation method and application thereof
CN118136938A
Fiber-connected metal organic framework (MOF) polymer solid electrolyte membrane and preparation method thereof, and lithium metal battery
CN118738540A
Cable guide apparatus for vehicle
KR1020230158988A
Electrolyte structure for metal batteries
US20160254567A1
Composite electrolyte membrane, fabrication methods and applications of same
US20180226682A1